CCAFS Conference Welcome Remarks - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Welcome remarks by: Dennis Garrity, ICRAF Director General Carlos Sere, ILRI Director General Rik Leemans, ESSP Chair Thomas Rosswall, CCAFS SC Chair Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya